2019
DOI: 10.1002/bit.27192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of micro and macroporous TFF membranes on product sieving and chromatography loading for perfusion cell culture

Abstract: Bioprocess intensification can be achieved through high cell density perfusion cell culture with continuous protein capture integration. Protein passage and cell retention are commonly accomplished using tangential flow filtration systems consisting of microporous membranes. Significant challenges, including low efficiency and decaying product sieving over time, are commonly observed in these cell retention devices. Here, we demonstrate that a macroporous membrane overcomes the product sieving challenges when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 28 publications
6
45
1
Order By: Relevance
“…Here, both Antibody and DNA average sieving coefficients were both reduced only when employing the 0.65-µm membrane (Figure 3). This finding confirms our previous (Pinto et al, 2020) With the membrane hydraulic permeability (shown in Table 1) and assuming uniform cylindrical pores, the mean pore radius (r p ) was determined using the equation as follows (Zeman & Zydney, 1996):…”
Section: Perfusion Membrane Assessmentsupporting
confidence: 85%
See 2 more Smart Citations
“…Here, both Antibody and DNA average sieving coefficients were both reduced only when employing the 0.65-µm membrane (Figure 3). This finding confirms our previous (Pinto et al, 2020) With the membrane hydraulic permeability (shown in Table 1) and assuming uniform cylindrical pores, the mean pore radius (r p ) was determined using the equation as follows (Zeman & Zydney, 1996):…”
Section: Perfusion Membrane Assessmentsupporting
confidence: 85%
“…Our previous study (Pinto, Napoli, & Brower, 2020) showed an integrated continuous bioprocess with practically nonproduct retention when employing macroporous (>1 µm pore size) perfusion membranes. This observation, corroborated by Wang et al (2017) and Wang et al (2019), highlights that microfiltration membranes retain particles within its pore size range, which leads to product sieving.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Disadvantages regarding the use of ATF systems in viral vaccine production due to an accumulation and eventual degradation of virions inside of the bioreactor may be alleviated by selection of membranes that are better suited for this type of application or specifically designed for virus production processes. Similarly to what was tested for membrane-based perfusion culture in recombinant protein production (Esclade et al 1991;Mercille et al 1994;Pinto et al 2019), different membrane chemistries, pore sizes, and properties such as hydrophobicity and surface charge should be characterized regarding product sieving and membrane fouling. For example, Genzel et al (2014) tested various polysulfone and polyether sulfone membranes for influenza virus production in perfusion mode.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the use of PS membranes can be equally important for related perfusion processes where expressed proteins are considered as product, but retained by PES membranes with a nominal cutoff of 0.2 μm (Karst, Serra, Villiger, Soos, & Morbidelli, 2016;Kelly et al, 2014). Alternatively, other studies identified the use of large-pore membranes of 2 μm and larger as a solution for production retention (Pinto, Napoli, & Brower, 2019;S. B. Wang, Godfrey, Radoniqi, Lin, & Coffman, 2019).…”
Section: Membrane Fouling Dynamics and Its Impact On Product Retentionmentioning
confidence: 99%